Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik terhadap Produktivitas Kerja Pegawai di UKM Tahu Sehat Cikampek - Husna Rozzaqiyah; Maman Suryaman; Risma Fitriani; Billy Nugraha (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to determine the effect of motivation intrinsic and extrinsic on work productivity in SMEs Tahu Sehat, located in the Village of Dawuan, Cikampek District, Karawang Regency. The method used in this research is Multiple Linear Regression. The type of research used is descriptive research and verification. The population in this research is employees of SMEs Tahu Sehat as many as 15 people. In addition, the sampling technique using saturated sampling. The data collection technique is done by using the parameters of the likert scale. The results of the questionnaire will be analyzed by the method of Multiple Linear Regression using SPSS Version 25. The results of the research prove that the influence between the variables of intrinsic motivation on work productivity. While extrinsic motivation has no effect. However, of the two variables influence simultaneously on work productivity.